2016
DOI: 10.1093/cid/ciw707
|View full text |Cite|
|
Sign up to set email alerts
|

Prediction of Congenital Cytomegalovirus Infection in High-Risk Pregnant Women

Abstract: This is the first prospective cohort study to suggest that the presence of CMV-DNA in the maternal uterine cervical secretion and ultrasound fetal abnormalities are predictive of the occurrence of congenital CMV infection in high-risk pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 23 publications
1
40
0
Order By: Relevance
“…borderline, 230-240; and positive, ≥240), but most of the results were significantly higher with mean 12 433 (1290-176 632) [25]. The serum titers of CMV IgG were not significantly different between the two groups -with and without congenital CMV, contrary to IgG avidity.…”
Section: Discussionmentioning
confidence: 75%
“…borderline, 230-240; and positive, ≥240), but most of the results were significantly higher with mean 12 433 (1290-176 632) [25]. The serum titers of CMV IgG were not significantly different between the two groups -with and without congenital CMV, contrary to IgG avidity.…”
Section: Discussionmentioning
confidence: 75%
“…The investigators mainly discussed from the viewpoint of the etiology of sexual transmitted diseases, uterine cervical cancer, or vertical transmission of these viruses from mothers to their infants following ascending infection or birth canal infection [13,14]. In our study, the percentage of positive PCR results for the cervical secretion in pregnant women with congenital CMV infection was 50% but only 5.8% in women without congenital CMV infection [8]. It is known that CMV shedding in the genital secretions may be prolonged after primary infection [15] and could also represent reactivation of latent virus [16].…”
Section: Cmv-dna Pcr Test Of Uterine Cervical Secretion May Be a Novementioning
confidence: 65%
“…We conducted a prospective cohort study to determine maternal clinical, laboratory, and ultrasound findings that effectively and noninvasively predict the occurrence of congenital CMV infection among CMV IgM-positive pregnant women, who are at high risk for congenital CMV infection [8]. The maternal clinical and laboratory findings, including CMV IgG AI, antigenemia assay (C7-HRP), PCR for the detection of CMV-DNA in the maternal serum, urine, and uterine cervical secretion (SRL, Tokyo, Japan) (positive, ≥1.0 × 10 2 copies/ml), and prenatal ultrasound findings, were evaluated.…”
Section: Commonly Used Methods For Prenatal Detection Of Fetuses At Hmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated, we have previously demonstrated that the presence of fetal ultrasound abnormalities was a significant predictive factor for congenital CMV infection in pregnant women with positive CMV IgM tests . We prospectively showed that the presence of ultrasound fetal abnormalities yielded a 50.0% sensitivity, a 97.5% specificity, a 61.1% positive predictive value and a 96.1% negative predictive value for when predicting congenital CMV infection.…”
Section: Maternal Screening For Predicting Congenital CMV Infectionmentioning
confidence: 98%